2016
DOI: 10.1080/17430437.2016.1225885
|View full text |Cite
|
Sign up to set email alerts
|

The fiddle of using the Paralympic Games as a vehicle for expanding [dis]ability sport participation

Abstract: In this paper we highlight the need to explore the excessive significance given to the Paralympic Games as a vehicle for the encouragement of participation of people with a disability within sport. The media spectacle around the games that the International Paralympic Committee (IPC) has worked tirelessly to develop has become, for policy makers and the public alike, a sufficient outlet for disability sport provision. We argue that the honourable goals of the IPC articulated through the ethos of Paralympism ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 20 publications
(18 reference statements)
0
20
0
2
Order By: Relevance
“…When allowed to participate, usually in adapted versions of mainstream sports, individuals with 'less-than-able' bodies are judged for their ability to perform similarly to their 'normal' counterparts and not for their distinctive capabilities. This is why sport has failed so far to promote true empowerment for participants with impairments and trigger a long-lasting cultural shift regarding disability [4,5]. A more empowering alternative would be to respect everyone's unique embodiment and judge performance in accordance to such distinctiveness.…”
Section: Introductionmentioning
confidence: 99%
“…When allowed to participate, usually in adapted versions of mainstream sports, individuals with 'less-than-able' bodies are judged for their ability to perform similarly to their 'normal' counterparts and not for their distinctive capabilities. This is why sport has failed so far to promote true empowerment for participants with impairments and trigger a long-lasting cultural shift regarding disability [4,5]. A more empowering alternative would be to respect everyone's unique embodiment and judge performance in accordance to such distinctiveness.…”
Section: Introductionmentioning
confidence: 99%
“…As we stated above, people with disabilities are often seen or viewed as a "drain" on public resources (Goodley, 2017;Goodley & Runswick-Cole, 2015) and sport is seen as one way of making the disabled body more productive through sport based rehabilitation and training (Howe & Jones, 2006;Howe & Silva, 2017;Jones & Howe, 2005;Purdue & Howe, 2013). Thus disability sport, is one "technology of government available" for disabled people to overcome "adversity" associated with their impairment (Braye, Dixon, & Gibbons, 2013), and arguably coaches work in sport is essential to supporting these objectives and thus re-enforcing and sustaining damaging "super crip narratives" 2 (e.g., Schalk, 2016;Shapiro, 1994).…”
Section: Sport Under the Conditions Of Neoliberal-ableismmentioning
confidence: 99%
“…Howe (2008a) has highlighted how functional classification allowed for a framework of competition that led to the reduction of classes, and the reduction of people with more complex impairments (such as those with Cerebral palsy in athletics) participating in Paralympic sport. More specifically, for this study, the issue is that if classification is uncritically questioned and implemented as the dominant organizing model of Paralympic sport at the grass roots level, inclusivity and equity will be diminished (Howe, 2008b;Howe & Silva, 2017;Richter, Adams-Mushett, Ferrara, & McCann, 1992). For example, the literature on swimming coaching has seldom explored how classification influences coaches working at the club and development level (cf.…”
Section: Classification Disability Sport and Swimmingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that sport provides a context that can challenge and influence the social 54 and cultural perceptions of disability and disabled people (Howe and Silva, 2016). This is 55 reinforced by binaries that often frame discussions about Paralympic and disability sport.…”
mentioning
confidence: 99%